2019
DOI: 10.1002/adhm.201901186
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species‐Scavenging Scaffold with Rapamycin for Treatment of Intervertebral Disk Degeneration

Abstract: The chronic inflammatory microenvironment is characterized by the elevated level of reactive oxygen species (ROS). Here, it is hypothesized that developing an ROS‐scavenging scaffold loaded with rapamycin (Rapa@Gel) may offer a new strategy for modulating the local inflammatory microenvironment to improve intervertebral disk tissue regeneration. The therapeutic scaffold consisting of ROS‐degradable hydrogel can be injected into the injured degeneration site of intervertebral disk (IVD) and can release therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…The ROS-responsive hydrogel was synthesized according to the previous protocol. 12,13 Gel was obtained by crosslinking poly(vinyl alcohol) (PVA) with a ROS-labile linker:…”
Section: Hydrogels Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The ROS-responsive hydrogel was synthesized according to the previous protocol. 12,13 Gel was obtained by crosslinking poly(vinyl alcohol) (PVA) with a ROS-labile linker:…”
Section: Hydrogels Preparationmentioning
confidence: 99%
“…The recent development of advanced biomaterials including inorganic materials, organic polymers, and their composites has shown great promise for accelerating the regeneration of damaged tissues. 5 , 8 , 12 , 13 Our previous studies revealed that silk fibroin loaded with MSCs promoted wound healing by regulating the polarization of macrophages, 13 and the ROS-scavenging hydrogels containing rapamycin regulated the inflammatory microenvironment of degenerated intervertebral discs and enhanced the regeneration of degenerated intervertebral discs. 12 Here, an in situ ROS scavenging hydrogel containing MSCs was constructed, which could modulate the local inflammatory microenvironment and improve the myogenic differentiation ability of MSCs, thereby promoting the regeneration of skeletal muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression was analyzed by western blot according to the standard instructions [ 30 ]. MC3T3-E1 cells were treated with PBS, 25 ng BMP-2, 100 μL BC, 100 μL BMP-2@BC containing the same amount of BMP-2 for 24 h. In detail, MC3T3-E1 cells were cultured in the lower compartment and BMP-2@BC were added to the upper compartment in a transwell system.…”
Section: Methodsmentioning
confidence: 99%
“…The recent development of advanced biomaterials including inorganic materials [ [15] , [16] , [17] ], organic polymers [ [18] , [19] , [20] , [21] , [22] , [23] , [24] ], and their composites [ 25 , 26 ] has shown great promise for accelerating bone reconstruction [ 27 , 28 ], providing alternatives bone remodeling methods [ [29] , [30] , [31] , [32] ]. Despite the outcomes of biomaterials for bone repair, many issues still hinder the clinical transformation from several aspects.…”
Section: Introductionmentioning
confidence: 99%